Improving child care in India through the development of the Questionnaire to Assess Needs of Children in Care (QANCC) - Kiran Modi; Emaya Anbalagan; Radhika Shroff; Nidhi Singhal (Scottish Journal of Residential Child Care)
India has around 20 million children living without families who need to be cared for through alternative forms of care. Udayan Care has an innovative group care model for children in need of care, utilising the indigenously developed LIFE (Living In Family Environment) strategy in its 13 UdayanGhars (Sunshine care homes). The model offers long-term permanent mentor parents to all children through the Carer team at its homes. Most often, children's direct input is not available to the management of care homes. To address this Udayan Care has developed the Questionnaire to Assess Needs of Children in Care (QANCC) to assess the needs of children under its care. The questionnaire is administered to children in a scientific manner every year to understand the basic/ fundamental, emotional, educational and interpersonal needs of the children aged 10-18 years under its care program with the goal of evaluating the extent to which these needs are being met from the perspectives of the children themselves. A census methodology is used on children aged between 10-18 years who have lived minimum of 6 months at the UdayanGhars. Over the years, we saw that on an average, 76.8% of the children feel that their needs are met; which is further stratified as follows: 92% of the children feel their basic fundamental needs are met, 80 % of the children feel their educational needs are met, 77% of the children feel that their Interpersonal needs are met, and 70% children feel their emotional needs are met. Areas of unmet needs have been identified to provide additional support specifically towards addressing them. The study allows children's participation in provide opinions on issues that directly impact upon them and the management of UdayanGhars consider these opinions while making decisions that affect their care; ultimately leading to improved standards of care at UdayanGhars.